Upaya Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPA Melalui Model Pembelajaran Scramble Kelas V di SD IT Plus Anbata Kecamatan Medan Sunggal, Kabupaten Deli Serdang T. A. 2022/2023 - Anggraini, Ayu; Lubis, Rizka Hidayah Husin; Harahap, Syarifah Ainun (Medan Resource Center, 2024)
This study aimed to enhance the learning outcomes in natural sciences through the implementation of the scramble learning model for fifth-grade students at SD IT Plus Anbata, Medan Sunggal, Deli Serdang. The research employed a Classroom Action Research (CAR) design with 30 students as participants. Data were collected through tests, observations, and documentation and analyzed using both qualitative and quantitative descriptive methods. The study established a success criterion of ?85% of students achieving a score of ?85. The findings indicate a significant improvement in students' learning outcomes after implementing the scramble learning model. In the first cycle, 80.33% of students reached the target score, which further increased to 90.36% in the second cycle. The improvement was attributed to modifications in cycle II, including smaller group sizes, more structured grouping, and rewards for quiet students. Since the success criteria met, the intervention was concluded in cycle II.